Korrelationen zwischen Änderungen des Windstresses, des Meeresspiegels und der Dichteschichtung im atlantischen Sektor des Südlichen Ozeans im Bezug auf den Jahresgang und auf zwischenjährliche Zeitskalen - Mengis, Nadine (2010)
Due to the increasing data coverage of the Southern Ocean by programs like the Argo Float Program, an analysis for this area concerning seasonal timescales is possible (Sallee). During the last three decades observations show an increase of the Southern Hemisphere westerlies (Visbeck (2007)). In most of the climate projections this trend tends to continue (Böning et. al. (2008)). By now the reactions of the Antarctic Circumpolar Current (Antarctic Circumpolar Current) concerning these changes in wind stress are not sufficiently clarified as well as in what timescales theses reactions might occur. In this bachelor thesis it is examined whether correlations can be found between changes in wind stress, in the steepness of the sea surface and stratification using CERSAT- scatterometer, AVISO - altimeter and Argo float data. These studies concern seasonal and interannual timescales. Therefore the chronological sequence of the mean wind stress from 40◦S to 55◦S, as well as the variation in time of the height differences of the sea surface and depth differences of the sigma27.2 density surface between 40◦S and 55◦S are observed. As a conclusion the development of the density surface on seasonal timescales arises to 61% from the influence of the wind stress. There is a time lag of two months between the wind stress and the reaction in the isopycnal tilt. The strength of the influence of the sea surface steepness is still uncertain. It is not possible to state clear positions concerning correlations on interannual timescales, as the time series of the float-data is too short (five years) for exact calculations.